The superalloys fundamentals and applications - Reed, Roger C. (Cambridge University Press, 2006)
Superalloys are unique high temperature materials used in gas turbine engines, which display excellent resistance to mechanical and chemical degradation. This book introduces the metallurgical principles which have guided their development. Suitable for graduate students and researchers, it includes exercises and additional resources at www.cambridge.org/9780521859042.
Keywords: Heat resistant alloys.; elektronické knihy; electronic books